1992
DOI: 10.1111/j.1469-7610.1992.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Psychological Functioning in Children and Adolescents with Inflammatory Bowel Disease: a Comparison with Children having Other Chronic Illnesses and with Healthy Children

Abstract: Psychiatric disorders and behaviour problems were found to be commoner in children and adolescents with inflammatory bowel disease (IBD) than in matched comparison groups with tension headache and diabetes as well as in healthy children. Depression, anxiety and low self-esteem were common. Many children denied their problems. This may be due to the type of illness, its social consequences and the embarrassment experienced by the children. Discrepancies were found between the children's and their mothers' repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
169
3
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(191 citation statements)
references
References 51 publications
15
169
3
4
Order By: Relevance
“…Depressed mood was also significantly associated with anxiety and impaired HRQOL and more IBD relapse in adults with IBD. 56 Several studies have found that adolescents with IBD are more depressed than children with other diseases [57][58][59][60] with rates up to 25%. 20 In adults with IBD, sleep quality was significantly inversely correlated with IBD activity 61 and could also have a significant impact on HRQOL.…”
Section: Psychosocial/psychological Factorsmentioning
confidence: 99%
“…Depressed mood was also significantly associated with anxiety and impaired HRQOL and more IBD relapse in adults with IBD. 56 Several studies have found that adolescents with IBD are more depressed than children with other diseases [57][58][59][60] with rates up to 25%. 20 In adults with IBD, sleep quality was significantly inversely correlated with IBD activity 61 and could also have a significant impact on HRQOL.…”
Section: Psychosocial/psychological Factorsmentioning
confidence: 99%
“…In children and adolescents, the symptoms and nature of CD might explain a higher risk for mental health disorders, including body image issues related to delayed growth and puberty, embarrassment, and isolation; perceived loss of control; and limited ability to participate in sports and school activities ( 23,24,35 ). Engstrom ( 36 ) found that psychiatric disorders and behavior problems were more common for children with IBD than for healthy children and children with diabetes or tension headache and that depression, anxiety, and low self-esteem were common in children with IBD. Th erefore, in addition to the eff ect of chronic comorbidities per se , CD has specifi c symptoms that are associated with great risk of psychiatric disorders in children.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Para los autores de esta perspectiva el síntoma se desencadena cuando los factores psicosociales actúan sobre factores de predisposición biológica al dolor (9), (22), (34), (35).…”
Section: Enfoque Biopsicosocialunclassified